Gut microbiota interacting with vitamin D but not anandamide might contribute to the pathogenesis of preeclampsia: a preliminary study - Xiao-Qiang Han; Xiao-Qiang Han; Hui-Hui Jiang; Meng-Ling Chen; Meng-Ling Chen; De-Yang Han; De-Yang Han; Su-Fen Zhou; Su-Fen Zhou; Jin-Wen Wang; Shu-Shen Ji; Ling-Yun Wang; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionPreeclampsia (PE) is a pregnancy-specific multisystem disorder and a leading cause of maternal and perinatal mortality globally. Despite numerous studies highlighting the potential roles of gut microbiota, anandamide (AEA), and Vitamin D (VitD) in PE, none have established them as reliable biomarkers for predicting disease onset. Moreover, their interactions in late-stage pregnancy women remain poorly understood.MethodsThirty-four preeclamptic patients (called PE group) and thirty-nine matched healthy late-pregnant women (called LP group) were involved in this case-control study. Fecal samples, which were used to acquire the diversity and composition of gut microbiota, were analyzed by 16S rRNA gene sequencing. Plasma AEA concentrations and serum VitD levels were determined by high-performance liquid chromatography-mass spectrometry (HPLC-MS) and liquid chromatography-tandem mass spectrometry (LC-MS/MS), respectively.ResultsIn this study, β diversity but not α diversity significantly differed between the LP and PE groups. Compared with the LP group, the relative abundances of Prevotella, Erysipelotrichaceae_UCG-003, and Dorea were increased dramatically in the PE group, whereas the relative abundances of Subdoligranulum, Parabacteroides, Bacteroides were significantly decreased in the PE group. Furthermore, women with PE had a substantially lower plasma level of AEA and a marked decrease in serum VitD compared to normal late-pregnant women. Lastly, although the serum level of AEA was not significantly correlated with VitD or any of the top 6 marker genera, VitD was significantly negatively correlated with the relative abundance of Dorea, a novel finding in this context.DiscussionThe gut microbiota profile of the PE group was significantly different from that of the LP group. Although no significant correlations were identified between the plasma AEA levels and serum VitD levels or any of the top 6 identified marker genera, a significant negative correlation was observed between VitD and Dorea, indicating VitD and gut microbiota have the potential to be combined targets for early diagnosis and management of PE.